Modeling Human Decision Making with Defeasible Logic Programming - Sapino, Maximiliano (2020)
Decision making is an active research topic in several disciplines and it can be studied in as many ways as different research areas face the problems in this field of study. In Computer Science, decision-making problems have been mainly tackled from the research field of Artificial Intelligence; and Argumentation has contributed with its unique strengths. In this work, following a pychological perspective we show the adequacy of Defeasible Logic Programming to model the Dictator Game by emulating the answers contained in a survey we conducted. The Dictator Game is a well-known problem belonging to the field of experimental economic studies related to human decision making. Moreover, the obtained model is simpler than other leading approaches in the area.